Defect Engineering Metal‐Free Polymeric Carbon Nitride Electrocatalyst for Effective Nitrogen Fixation under Ambient Conditions. Issue 32 (15th July 2018) - Lv, Chade; Qian, Yumin; Yan, Chunshuang; Ding, Yu; Liu, Yuanyue; Chen, Gang; Yu, Guihua
Abstract: Electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions provides an intriguing picture for the conversion of N2 into NH3 . However, electrocatalytic NRR mainly relies on metal‐based catalysts, and it remains a grand challenge in enabling effective N2 activation on metal‐free catalysts. Here we report a defect engineering strategy to realize effective NRR performance (NH3 yield: 8.09 μg h −1  mg −1 cat., Faradaic efficiency: 11.59 %) on metal‐free polymeric carbon nitride (PCN) catalyst. Illustrated by density functional theory calculations, dinitrogen molecule can be chemisorbed on as‐engineered nitrogen vacancies of PCN through constructing a dinuclear end‐on bound structure for spatial electron transfer. Furthermore, the N−N bond length of adsorbed N2 increases dramatically, which corresponds to "strong activation" system to reduce N2 into NH3 . This work also highlights the significance of defect engineering for improving electrocatalysts with weak N2 adsorption and activation ability. Abstract : Carbon nitride materials : An efficient metal‐free polymeric carbon nitride catalyst has been obtained by a defect‐engineering strategy for the electrocatalyic ammonia synthesis. The metal‐free catalyst has a high density of nitrogen vacancies which are as active sites responsible for chemisorption and activation of N2 and lead to a high NH3 yield and Faradaic efficiency.